Relationships between Robot's Self-Disclosures and Human's Anxiety toward Robots - Nomura, T.; Kawakami, K. (2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2011)
The research aimed at investigating how self-disclosure of robots affects humans' anxiety and behaviors toward the robots. A psychological experiment (N = 39), comparing between the conditions of no-self-disclosure, positive self-disclosure, and negative self-disclosure from a small-sized humanoid robot, found that the subjects' anxiety toward communication capacity of robots was stable before/after positive self-disclosure from the robot although this anxiety increased under the other conditions. On the other hand, self-disclosure from the subjects was independent to the conditions of the robot's self-disclosure, and the subjects originally having hither anxiety toward discourse with robots before the interaction performed negative self-disclosure toward the robot.